A Formal Language to Convey Linguistic Information. A Study in Practical Logic - Tsinman, Leonid (Meta, 1995)
AbstractThe author discusses problems of treating formal languages to present linguistic data in machine translation systems or linguistic interfaces for man-computer communication.